An evaluation on the effectiveness of Sarawak Shell Berhad offshore installation managers and their deputies in handling emergencies - Al-Zadjally, Saeed Khamis Juma (2001)
An evaluation is effectively conducted and analyzed to determine the strengths, weakness, and provide quality improvements for Offshore Installation Managers who handle all crisis and emergencies response management on SSB offshore oil and gas platforms. The primary objective of this project was to test the evaluation on the effective roles of offshore installation managers and their deputies, all of whom are holding very critical positions and are respectively responsible for effectively maintaining a state of readiness for all oil and gas production and terminal locations within SSB / SPC organization. At the same time, it is aimed to develop specific operating guides on the general response to oil and gas platform potential emergencies scenarios. The methodology for OIMs effective roles evaluation too, is using the Microsoft Excel Spreadsheets by statistically analyzing the data collected from survey questionnaire sent to all OIMs and their deputies who are fully responsible for the management of the emergency situations and real incidents. This is selected for the evaluation because it is a high priority and HSE critical roles and responsibilities for the OIMs and their deputies and also no such evaluation has formally been initiated Data collected were based on the measurements of seven valuable dimensions / sections as stipulated in the research questionnaire sent to respondents. The effective roles performance of the overall and each component were interpreted from the total and individual components ‘score’. A survey was conducted using questionnaire consisting of seven sections and, the questionnaire were sent to all the OIM, SA and WS who had undergone the training program of managing major emergency. From the responses, the data were processes based in the statically analyzing the data collected using Microsoft Excel. Statistically analyzing the data collected using Microsoft Excel as evaluation tool was indeed a simple and practical evaluating tool, as calculations of the measurements of the testing methodology and component ‘score’ do not require complex mathematics or any software applications. As for monitoring the quality of OIMs and their deputies effective roles and response measures in managing major emergency or real incident, the strong and week components were easily identified from the variation in theory of the scores, “flagging” potentially important issues so that further evaluation inquiry can be targeted to improve the overall quality of the OIMs and their deputies. In conclusion, statistically analyzing the data collected using Microsoft Excel as a testing methodology and evaluation tool, is indeed recommended methodology for quality monitoring and improvement system, and as objective measure to prioritize on the issues of effective roles of offshore installation managers and their deputies in appropriately managing various potential of emergency situations. In addition to this, analyzing of sixty three observations remarks ( Appendix D ) made as result of conducting emergency drills for two years on one of SSB offshore platform, indeed indicated that there is real need for specific operating guides on the general response to oil and gas platform potential emergency scenario must be developed for the OIMs and their deputies to refer to during emergencies situations and these specific operating guides should be left on site for offshore site management teams to use in the event of any emergency.